Visual-based embedding systems with targeted secret disclosures and applications. (10th December 2008) - Wang, Shiuh-Jeng; Lin, Jian-Yi; Ke, Hung-Jui; Lin, Shu-Wen
In this paper, a VWC-system is proposed. In the system, the embedded information can hold the secret for the encryption key. The system adopts the technique of frequency-domain watermarking and visual cryptography, respectively. Furthermore, the embedded part is only a share, meaning a portion of the watermark generated from a chosen KFI. The remaining shares not used in the embedding procedure are kept until the extraction procedure in order to reveal the targeted secret or copyright watermark shown in the message of the watermark image. Another feature is the key could be easily applied in a symmetric-key cryptosystem for a common key agreement via a public channel.